(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main purpose of conducting this research is to study the consuming pattern of gold jewellery by ruralbachelorette in Kanyakumari district. The objective of the study is to get insight about the rural bachelorette’sconsuming pattern, reason for buying gold jewellery and factors influencing while purchasing gold jewellery. Gold is a precious metal and also the wealth of an individual is calculated based on the amount of gold one possesses. It is considered as a sign of one’s wealth and opulence. An Indian bachelorette receives gold as a blessing for a happy and healthy married life. Even when gold rates are skyrocketing, Indians wouldn’t refrain from buying or investing in gold especially when the excuse is for wedding. Gold jewellery definitely the most precious gift for the bachelorette as well. Therefore this study assumes significance and the researcher wants to explore and analyses the consuming pattern of bachelorette, reasons for buying, and different types of gold jewellery preferred by the bachelorette. A well-structured questionnaire is prepared to collect the data from the respondents. A sample of 600 rural bachelorette in Kanyakumari district is selected by using convenient sampling technique. This study will help the owners of the jewellery shops to know about the consuming pattern of the ruralbachelorette in order to take remedial measures.